Contemporary Human Resource Practices in Indian IT Industry: A Comparative Analysis of Major Players - Singh, Apoorva (The journal of contemporary issues in business and government, 2021)
Previous studies have shown that practices adopted by the organizations directly or indirectly lead to various organization and employee specific outcomes in terms of productivity, performance and competitiveness. The present study explores such HR practices adopted by India’s major IT players and makes a comparative analysis. Using data from 375 professionals of selected Indian IT companies, the study found that selected companies makes effective use of contemporary human resource practices viz. work from home, flexible work hours and sabbatical leaves for employees. The results of the study further indicated that of all the selected companies, HCL ranks top when it comes to implementing contemporary HR practices. The study concluded that employee related organizational objectives can be achieved with a combination of traditional HR practices and contemporary methods. The high performing firms in industry uses the best of practices to find, attract, retain and engage the talent of the firm.